Julgar a cada um o que é seu: justiça e criminosos nos domínios portugueses da Fronteira Platina (1777ca.-1810ca.) - Piccoli, Andréia Aparecida (2019)
This research is about the dealing of Justice and the criminals on Portuguese domains of the Río de la Plata frontier (1777ca. - 1810ca.), mainly in military departments of Rio Grande and Rio Pardo. During the XVIII century, the Captaincy of the Rio Grande de São Pedro do Sul constituted a kind of border between the domains of Portuguese and Spanish monarchies in southern America. In process of annexation to the Portuguese Empire, the captaincy was composed of a singular judicial administration, due to the incipiency of magistrates of the Crown’s administrative nets in this territory, being constituted then by the local Justice, captain-general and governor, military helms of the aforementioned departments and district commanders, in a sense of military hierarchy. A seldom studied portion of this society, criminals were mostly individuals of low social extracts – In a society in which the sense of justice itself validated the inequality before the law –; above all individuals who employed illegal practices for the improvement of their lives, in a historical juncture in which crime was not considered a regular occupation. As punishment for their transgressions, criminals had their bodies punished and were forced to work for his Most Faithful Majesty. For the accomplishment of these practices, material bases of power were utilized, such as dungeons in forts and guarded prisons, the irons to torture and bind individuals, and the routes of transport and information. Moreover, such conjuncture was only made possible by the social validation of this Justice, specially by the military commanders' political and social notoriety, stemming from their roles as keepers of public order e territorial defenders of the Portuguese Empire, the latter serving as recognition from the Crown. In spite of criminals, the corollary of this Justice was the subordination of individuals and the maintenance of current social ordination.